2015
DOI: 10.1089/g4h.2014.0126
|View full text |Cite
|
Sign up to set email alerts
|

Active Gaming Among High School Students—United States, 2010

Abstract: Four out of 10 U.S. high school students report participating in active gaming. Active gamers tend to spend more time watching DVDs or TV, meet guidelines for physical activity, and/or be overweight or obese compared with nonactive gamers. These findings may serve to provide a baseline to track active gaming in U.S. youth and inform interventions that target sedentary behaviors and/or physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…When students are taught various lessons that meet their interests and provide new experiences, they are more likely to be engaged and motivated in PE. Additionally, despite the popularity of team sports among adolescents, a study showed that only 13% of adults participate in team sports (Song et al, 2015). By teaching team sports exclusively, PE programs cannot help students prepare for future PA participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When students are taught various lessons that meet their interests and provide new experiences, they are more likely to be engaged and motivated in PE. Additionally, despite the popularity of team sports among adolescents, a study showed that only 13% of adults participate in team sports (Song et al, 2015). By teaching team sports exclusively, PE programs cannot help students prepare for future PA participation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the preference of team sports participation varies based on the age group and gender (Harrison & Narayan, 2003), team sports attract many individuals. Song, Carroll, Lee, and Fulton (2015) found that team sports were listed as one of the most favorite physical activities among adolescents and second most popular for male adults. In secondary PE, team sports have been a predominant content area because they can easily accommodate large class sizes, promote social and cooperative behaviors, and develop cardiorespiratory endurance (Coakley, 2017).…”
mentioning
confidence: 99%
“…La mayoría de niños sedentarios practican menos actividad física, considerándose el sedentarismo la antítesis de la actividad física debido a que las horas sedentarias están quitando horas de actividad física a lo largo del día y por tanto asociado a problemas de salud debido a la inactividad prolongada (Marshall, Biddle, Gorely, Cameron y Murdey, 2004). Sin embargo, con la introducción de los videojuegos activos como un método de entretenimiento alternativo, facilita que los niños no sean sedentarios cuando disfrutan de ellos, tal y como indican autores como Song, Carroll, Lee y Fulton (2015).…”
Section: Discussionunclassified
“… 12 Among US high school students, 4 of 10 report participating in active gaming. 13 At present, organized esports is becoming a competitor to replace recreational sports participation among the youth.…”
Section: Introductionmentioning
confidence: 99%